Clinical efficacy of ERAS plus enteral nutrition in patients undergoing laparoscopic surgery for gynecologic malignancies - Xia, Huan; Zhang, Yaoyang; Su, Cuiying; Zhou, Min; Liu, Wenying; Chen, Jiming; Lu, Bingying (Frontiers in Medicine, 2025)
ObjectiveTo enhance postoperative recovery in gynecological malignancies by evaluating the clinical efficacy and safety of Enhanced Recovery After Surgery (ERAS) combined with enteral nutrition.MethodsThis study included 127 patients with gynecological malignancies treated at Zigong Fourth People’s Hospital between January and December 2022. Based on patient preference, 60 were placed in the study group (ERAS + enteral nutrition) and 67 in the control group (traditional care). The two groups were compared on postoperative protein levels, electrolyte balance, and recovery indicators, including the time to first anal exhaust, defecation, and hospital stay duration. Additionally, preoperative thirst, hunger, anxiety scores, postoperative complications, and total hospitalization costs were evaluated.ResultsThe study group had higher postoperative total protein (66.59 ± 10.97 g/L) and albumin (43.47 ± 51.27 g/L) than the control group, with a significantly lower incidence of hypoproteinemia (18.33% vs. 50.75%, p < 0.05). There were no significant differences in hemoglobin, lymphocyte count, or electrolytes. The study group recovered bowel function earlier than the control group, with significant differences in defecation time (p < 0.05). No significant differences were observed in anal exhaust time, hospital stay, complications, or total costs. The study group had better anxiety, thirst, and hunger scores (p < 0.05).ConclusionERAS combined with enteral nutrition is safe and effective for gynecological cancer surgery, reducing hypoproteinemia, promoting gastrointestinal recovery, and improving patient experience and psychological well-being.